2019
DOI: 10.1523/jneurosci.3047-18.2019
|View full text |Cite
|
Sign up to set email alerts
|

Tonic Suppression of the Mesolimbic Dopaminergic System by Enhanced Corticotropin-Releasing Factor Signaling Within the Bed Nucleus of the Stria Terminalis in Chronic Pain Model Rats

Abstract: Although dysfunction of the mesolimbic dopaminergic system has been implicated in chronic pain, the underlying mechanisms remain to be elucidated. We hypothesized that increased inhibitory inputs to the neuronal pathway from the dorsolateral bed nucleus of the stria terminalis (dlBNST) to the ventral tegmental area (VTA) during chronic pain may induce tonic suppression of the mesolimbic dopaminergic system. To test this hypothesis, male Sprague Dawley rats were subjected to spinal nerve ligation to induce neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…The present study revealed that the frequency of sIPSCs in VTA-projecting dlBNST neurons was enhanced in rats exposed to CMS, an animal model of depression, as observed in our previous study using an animal model of chronic pain [8]. Enhanced inhibitory transmission to VTA-projecting dlBNST neurons may be a neuronal mechanism common to depression and chronic pain that causes depression-like behaviors.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The present study revealed that the frequency of sIPSCs in VTA-projecting dlBNST neurons was enhanced in rats exposed to CMS, an animal model of depression, as observed in our previous study using an animal model of chronic pain [8]. Enhanced inhibitory transmission to VTA-projecting dlBNST neurons may be a neuronal mechanism common to depression and chronic pain that causes depression-like behaviors.…”
Section: Discussionsupporting
confidence: 88%
“…We previously reported that enhanced inhibitory synaptic inputs to VTA-projecting dlBNST neurons observed in the animal model of chronic pain were suppressed by NBI27914, a CRF type I receptor antagonist [8]. However, the current study showed that NBI27914 tended to suppress the CMS-induced facilitation of inhibitory synaptic inputs to VTA-projecting dlBNST neurons, but the effects were not significant, suggesting the different neuroplastic mechanisms for the enhancement of inhibitory synaptic inputs to VTA-projecting dlBNST neurons between CMS and chronic pain.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Elegant work from the Minami group has demonstrated that CRF can be released in the BNST over the course of an hour following formalin injection (Ide et al, 2013), so it is possible that some of the changes we observed over time in our in vivo imaging studies were due to local release of CRF. This is a particularly interesting possibility in the context of chronic pain, since long-term injury has been reported to drive functional upregulations of CRF signaling and putative CRF activity in the BNST (Rouwette et al, 2012;Ide et al, 2013;Takahashi et al, 2019;Hara et al, 2020).…”
Section: Contrary To the Anti-nociceptive Effects Observed With Acutementioning
confidence: 99%